ANALISIS PENGARUH PERTUMBUHAN PENDUDUK TERHADAP HARGA TANAH DI KELURAHAN KWAMKI DISTRIK MIMIKA BARU KABUPATEN MIMIKA - Siti Ruchmawati; Antje Tuasela (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2017)
The high population growth is caused by birth, death and migration factor, resulted the needs of the land can not be avoid. This research aims to know the effect of population growth towards land prices in Kwamki Village, Mimika Baru District, Mimika Regency from 2006 to 2010. The data used in this research was the population growth data of Mimika Regency 2006 – 2011 that announced by cooperation between the office of development planning and the office of statistic centre in Mimika Regency. The research applied quantitative method and statistical analysis is the simple regression analysis. The result of coefficient of determination analysis (R2) shows that the influence exterted of population growth (X1) on the land prices is 0,160, which means the population growth variable (Y), can explain the variable of the land about 16%, while the rest, as much as 84% is influenced by other variables which are not revealed in this research.